System failures, knowledge bases and regional innovation policies. - Martin, Roman; Trippl, Michaela (Routledge, 2014)
Regional innovation strategies rank at the top of public policy agendas today. There is a widespread consensus in both academic and policy circles that standardized "best practice" innovation policy models suffer from severe limitations and major shortcomings. The recent literature is replete with claims that regional innovation policies should be placebased and context-sensitive, taking into consideration the specificities of regions and their distinctive preconditions and capacities for innovation. Various conceptual approaches and theories support such a view. This paper discusses two concepts that have a particularly strong potential for informing customized regional innovation policies: the regional innovation system (RIS) approach and the knowledge base concept. The RIS literature highlights the importance of the organizational and institutional setting of a region and suggests that system deficiencies or failures should constitute the starting point for designing regional innovation policies. The differentiated knowledge base approach stresses that regional industries can differ strongly in their underlying knowledge bases and, as a consequence, in their policy needs. We elaborate on the policy implications that originate from these concepts and argue that tailor-made regional innovation policies should consider both region-specific institutional set-ups and knowledge bases. Focusing on peripheral regions, we outline how such an integrated framework can inform customized regional innovation policies.
Keywords: Regionalplanung; Regionale Disparität; Randzone; Regionalentwicklung; Regionalwirtschaft; Wirtschaftsförderung; Innovation; Peripherie; Innovationsförderung; Handlungsfeld; Innovationspolitik; Wissensökonomie